Rhinocerebrocutaneous mucormycosis caused by Mucor species: A rare causation - Lunge, Snehal Balvant (Indian Dermatol Online J, 2015)
Rhinocerebral mucormycosis is the most common form of mucormycosis occurring commonly in patients of diabetic ketoacidosis. Fungi of the order Mucorales belong to six families, among whom Rhizopus is the most common, while Mucor is a rare cause. We report a 45-year-old female with uncontrolled diabetes mellitus diagnosed to have rhinocerebrocutaneous mucormycosis caused by Mucor species. The diagnosis was confirmed on histology and culture. A high-index of suspicion is required for early diagnosis and timely initiation of therapy to optimize the outcome. Our patient succumbed to her infection.